2022
DOI: 10.1002/prp2.1008
|View full text |Cite
|
Sign up to set email alerts
|

Prescribing cascades in community‐dwelling adults: A systematic review

Abstract: The misattribution of an adverse drug reaction (ADR) as a symptom or illness can lead to the prescribing of additional medication, referred to as a prescribing cascade. The aim of this systematic review is to identify published prescribing cascades in community‐dwelling adults. A systematic review was reported in line with the PRISMA guidelines and pre‐registered with PROSPERO. Electronic databases (Medline [Ovid], EMBASE, PsycINFO, CINAHL, Cochrane Library) and grey literature sources were searched. Inclusion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 135 publications
0
16
0
Order By: Relevance
“…We performed an analysis of all prescribing cascades identified by our previous systematic review as relevant to ambulatory care, 18 for which one or more confirmatory studies had found a statistically significant association between an index and a marker drug. We limited our analyses to cohort, case–control, or prescription sequence symmetry analyses (PSSA) 19 with pre‐specified hypotheses, and thus excluded both cross‐sectional as well as exploratory studies aiming to identify new signals of prescribing cascades (as opposed to confirming pre‐specified ones) 20 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We performed an analysis of all prescribing cascades identified by our previous systematic review as relevant to ambulatory care, 18 for which one or more confirmatory studies had found a statistically significant association between an index and a marker drug. We limited our analyses to cohort, case–control, or prescription sequence symmetry analyses (PSSA) 19 with pre‐specified hypotheses, and thus excluded both cross‐sectional as well as exploratory studies aiming to identify new signals of prescribing cascades (as opposed to confirming pre‐specified ones) 20 .…”
Section: Methodsmentioning
confidence: 99%
“…Considering these domains, we differentiated between four levels of evidence (from I = strong to IV = poor) as shown in Table 1.Methodological quality (risk of bias) was assessed for each study using the appropriate Joanna Briggs Institute (JBI)—Critical Appraisal checklist 21 (Box S1). Assessments were conducted by at least two reviewers independently, with disagreements resolved by discussion or consultation of a third reviewer where necessary, as detailed in our previously published systematic review 18 . The quality score of each individual study was calculated, where the cut‐off score for high‐quality study (low risk of bias) was ≥70%, for moderate‐quality study design 50%–69%, and for low‐quality (high risk of bias) study design <50% (Table S1 and S2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Many prescribing cascades have been described in the literature and several reviews have been published [ 3 , 6 – 8 ]. One of the reviews was limited by including only prescribing cascades that were identified through a prescription sequence symmetry analysis [ 7 ], whereas another review identified prescribing cascades occurring with pain medication [ 6 ] .…”
Section: Introductionmentioning
confidence: 99%